Advances in engineering materials and applied mechanics proceedings of the 5th International Conference on Machinery, Materials Science and Engineering Application, (MMSE 2015), Wuhan, Hubei, China, 27-28 June 2015 - Zhang, Guangde; Gao, Quanjie; Xu, Qiang
With the rapid development of Machinery, Materials Science and Engineering Application, discussion on new ideas related mechanical engineering and materials science arise. In this proceedings volume the author(s) are focussed on Machinery, Materials Science and Engineering Applications and other related topics. The Conference has provided a valuable opportunity for researchers ,scholars and scientists to exchange their ideas. The conference organization aims to strengthen national academic exchanges and cooperations in the field, promote the rapid development of machinery, materials science and engineering application, effectively improve academic status and international influence of China's machinery, materials science and engineering applications and play an active role to reduce the distance between domestic related disciplines and international themes